Photocatalytic Performance Of A Slurry And Immobilized TiO2 Degussa P-25 For The Degradation Of Aqueous Organic Pollutants Under 45W Compact Fluorescent Lamp - Zain, Salmiah Md (2012)
A simple and effective dip coating method was used for immobilizing P-25 powder onto glass plates using epoxidized natural rubber (ENR)/ poly (vinyl) chloride (PVC) blend as adhesives. The reusable P-25/ENR/PVC catalyst plate could avoid tedious filtration step in aqueous slurry system. Based on the photocatalytic removal rate of RR4 and the adhesion of the P-25 formulation, the optimum ratio of ENR to PVC for the immobilization was determined as 1:2. The immobilized P- 25/ENR/PVC catalyst plate was characterized using SEM, TGA and BET analyses. Due to the low durability of the organic polymer, ENR and PVC applied in this system were prone to be degraded and resulted in the detection of chemical oxygen demand (COD) values in the treated ultrapure water. By washing procedure through irradiation process could stabilize the polymer blend and increase the BET surface area of the immobilized catalyst. The initial pH of RR4 solution, amount of catalyst loading, aeration rate, and the initial concentration of RR4 dyes were found to influence the pseudo-first order rate constant of the photocatalytic activities of RR4. The presence of aeration as oxygen source promoted the photocatalytic removal. The optimum catalyst loading was determined at 1.500 ± 0.005 mg cm-2 and the photocatalytic degradation of RR4 was highest at acidic condition. The increase of the initial concentration of the RR4 dyes decreased the degradation rate. The role of adsorption and the chemical structure of the organic pollutants affected the photocatalytic degradation rate. The degradation rate for RR4 and phenol were much slower using immobilized system. However for the degradation of MB, immobilized system was found to be much faster than the suspended system. The immobilized P-25/ENR/PVC/5h catalyst plate can be reused for many repeated cycle of applications. The mineralization of organic pollutants was also evaluated by measuring COD, the changes of pH of the solution, and the evolution of nitrate, sulphate and chloride anions of the pollutants. It was observed that the decolorization process of the RR4 and MB dyes were always faster than their mineralization process, however the decomposition of phenol was almost identical with their mineralization process.